REVIEW OF ISLAMIC LAW ON THE STATUS OF MOSQUE IMAMS AS ZAKAT MANAGERS IN TIROANG DISTRICT, PINRANG REGENCY (Analysis of MUI Fatwa No. 8 of 2011) - Muh. Aidil Fitra, Aidil; M. Thahir Maloko; Mahmudah Mulia Muhammad (El-Iqthisadi, 2025)
Abstract The management of zakat in Tiroang District, Pinrang Regency is managed by the Imam of the mosque and in its management does not have legality from the government, as explained by Madeali that "the one who manages zakat in Tiroang District, Pinrang Regency is an Imam of the mosque". This is certainly not in accordance with the concept of amil zakat according to MUI Fatwa Number 8 of 2011 where amil is an individual or group appointed by the government to manage the implementation of zakat; or individuals or groups formed by the maysarakat and then authorized by the government to manage the implementation of zakat worship. The purpose of this study is to find out the practice of zakat management in Tiroang District, Pinrang Regency and to find out the provisions of Islamic law on the status of mosque imams as zakat managers in the area. This type of research is classified as qualitative with the approach used, namely the normative theology approach (Syar'i) and the empirical approach. The data collection methods carried out in this study are observation, interviews and documentation. The results of the study show that the management of zakat in Tiroang District, which is managed by the imam of the mosque, has been running for generations. The form of zakat management in Tiroang District is starting from receiving zakat from muzakki, then recording and distributing it to mustahik zakat. Regarding reporting, the imam of the mosque did not report to any party. In his duties as a zakat manager, the Imam of the Tiroang District mosque always takes a share of zakat of around 10%. The management of zakat carried out by the Imam of the mosque in Tiroang District according to Islamic law is legal. Muzakki has lost his obligation. However, regarding the status of the imam of the mosque in Tiroang District as a person who manages zakat cannot be called a zakat manager (amil zakat) as explained in the provisions of Islamic law that a zakat manager (amil zakat) is someone who is given the task/appointed by the government to take care of all matters related to zakat. This is because the Imam of the mosque in Tiroang District is not appointed/given the task by the government to manage zakat, but only based on the community's agreement to manage zakat. Keywords: Islamic Law, Imam of the Mosque, Zakat Manager